L’archivio di Massimo Fagioli: scritti e documenti dai primi anni Sessanta a Istinto di morte e conoscenza - Verdi, Orietta; Armando, David (Il sogno della farfalla, 2022)
On the 50th anniversary of Death instinct and knowledge’s publication, this article offers an overview of the archival documentation of the Sixties and early Seventies, now stored in Massimo Fagioli’s Archive. The archive, owned by the heirs, is preserved at Massimo Fagioli Foundation which has begun a work of cataloguing and inventory. The documents presented in this article includes some writing composed close to the book’s publication. On one hand, these articles confirm that the volume was written in a short time at the end of the 1970, being the result of a long reflection fueled by the reading of many articles and from the clinical practice with patients and colleagues. Finally, these documents allow to investigate the events related to the book’s publication and the reactions provoked.